Produção capitalista e reprodução social: a questão de gênero a partir das vivências de mulheres de uma mesma família - Lima, Ana Beatriz Medeiros (2024)
The purpose of this study arises from the encounter between the researcher and the life history of a a black woman who is also a mother and an informal worker. In observing similarities between her biographical narrative and the references to the trajectories of her mother and daughter, in a previously conducted study, this investigation takes shape from a concern about the centrality of labor performed in the realm of social reproduction, alongside the restriction of opportunities within the productive sectors. Thus, the main objective of this research is to analyze how the relationship between exploitation and oppression persists, updates, and faces resistance in the daily lives of women from the same family. The dialogue between the analytical frameworks of the Historical-Cultural Psychology and the Social Reproduction Theory grounds the reflection on how social structures organize social relations, based on specific and differentiated conditions related to the interplay between the exploitation of the working class and the oppressions of gender and race. It therefore guides the understanding of the mediations underlying the constitutive relations of the subjects' experiences as historical beings. Framed as a qualitative research guided by historical-dialectical materialism, the process of mediation between singularity and universality is revealed through the particularities of these women’s lived experiences. Considering the complex and contradictory movement of how these experiences are constituted, the subject is not seen merely as a reactor to the logic of materiality that articulates exploitation and oppression; the processes that indicate change in the direction of perceptions and projections as subjects in the world are analyzed with equal attention to the reproduction of structural relations, through the unveiling of the symbolic, cognitive, and affective singularities of the participants. In approaching the field, where indepth interviews were conducted based on life histories, these singularities pointed to a specificity of the field, prompting a shift in the method chosen for data analysis. Thus, the material analyzed is organized into three areas of tension: (1) experiences of care vs. vulnerability situations; (2) senses of self vs. experiences of social relations; and (3) conditions of the concrete vs. abstractions about the future. The analysis of the updating of the relationship between exploitation and oppression, based on the production-reproduction unity, indicated that more than conflicting social roles and subsequent resolutions, what organizes lived experience are contradictions situated in different fields of tension, represented here in the three analytical nuclei. In conclusion, we argue that the specific analysis of these contradictions presents an important path in constructing a praxis of psychological Science situates, first, in critiquing the exclusionary logic by which the capitalist totality operates, shaping different experiences among various subjects and social groups, and, essentially, towards the emancipation, considering the creative and creative character of the human condition.